2020
DOI: 10.3390/ijerph17041149
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy as a Shared Capacity: Does the Health Literacy of a Country Influence the Health Disparities among Immigrants?

Abstract: Health literacy (HL) is an individual ability as well as a distributed resource available within an individual’s social network. We performed an explorative study assessing the role of HL as the country-level ecological variable in predicting the health disparities among immigrants. Country-level HL data were obtained from the publicly available first European Health Literacy Survey reports. Individual-level data on citizenship, perceived health status, body mass index, smoking habits, physical activity and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…The association between higher education and higher screening participation is in line with previous national findings from Finland [46,47] and self-reported screening test uptake in Finland, here mainly observed among the Kurds [21], and with other international studies [11,24,37]. Higher education and health literacy may thus be associated [72,73]. Additionally, when we used employees as a reference, no differences between the employed and women taking care of children at home emerged, except for students and retirees, who exhibited lower screening participation.…”
Section: Discussionsupporting
confidence: 90%
“…The association between higher education and higher screening participation is in line with previous national findings from Finland [46,47] and self-reported screening test uptake in Finland, here mainly observed among the Kurds [21], and with other international studies [11,24,37]. Higher education and health literacy may thus be associated [72,73]. Additionally, when we used employees as a reference, no differences between the employed and women taking care of children at home emerged, except for students and retirees, who exhibited lower screening participation.…”
Section: Discussionsupporting
confidence: 90%
“…However, most women in our study had heard about the Finnish screening program and were aware of its importance and had participated in screening. Having a sound understanding of health information and what it entails seemed to raise the women’s motivation to utilize the CCS service; health literacy and healthcare service utilization may thus be related [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association with citizenship in our study is in agreement with a previous study from the U.S. showing higher PA among migrants with U.S. citizenship [ 45 ]. A recent study from the EU also showed significantly lower PA levels among nationals of non-EU countries in Austria compared to Austrian nationals [ 46 ]. Participants who chose German as the questionnaire language were more likely to be in the stable active trajectory, which is supported by a systematic review, including a wide range of countries, showing that poor knowledge of the language of the host country was claimed as having a large impact on PA as a barrier to get access to or understand PA recommendations [ 29 ].…”
Section: Discussionmentioning
confidence: 99%